2002
DOI: 10.1124/jpet.102.038612
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NO in the Endothelium-Independent Relaxing Effects ofNω-Hydroxy-l-arginine and Other Compounds Bearing a C=NOH Function in the Rat Aorta

Abstract: The mechanisms of vasorelaxation elicited by N -hydroxy-Larginine (L-NOHA) and other compounds bearing a CϭNOH function and the structural determinants governing this effect were investigated in rat aorta. L-NOHA, formamidoxime, five aromatic monosubstituted amidoximes, and one aromatic monosubstituted ketoxime elicited relaxation in endothelium-denuded rings. N-Hydroxyguanidine and substituted N-hydroxyguanidines were markedly less active. Relaxations induced by L-NOHA and by the most active studied compound,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…It has been reported that non-amino acid compounds sharing the R 2 C=NOH group can produce nitric oxide synthase-independent relaxation in endothelium-denuded aortic rings of rats [10,[14][15][16]. In addition, the mechanisms underlying the effects of exogenous nitrovasodilators are predominantly mediated by cyclic guanosine monophosphate (cGMP), as a result of the activation of soluble guanylyl cyclase [17,18].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that non-amino acid compounds sharing the R 2 C=NOH group can produce nitric oxide synthase-independent relaxation in endothelium-denuded aortic rings of rats [10,[14][15][16]. In addition, the mechanisms underlying the effects of exogenous nitrovasodilators are predominantly mediated by cyclic guanosine monophosphate (cGMP), as a result of the activation of soluble guanylyl cyclase [17,18].…”
Section: Figurementioning
confidence: 99%
“…Administration of Oxime S1 (10,15,20 and 30 mg/Kg, i.v., randomly) induced dose-dependent hypotension (−10 ± 3, −18 ± 4, −22 ± 3 and −32 ± 6 mmHg, respectively) associated to increase in the heart rate (8 ± 3, 15 ± 3, 21 ± 4 and 25 ± 4 bpm) (Figure 2). …”
Section: Oxime S1 Reduces Blood Pressure In Conscious Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well reported in the literature that L-NOHA (48) and other NO-donors can also induce NOS-independent relaxation in endothelium-denuded arteries and that this relaxation involves the NO-cGMP pathway (48,49). Since both, NO formation (measured as NO x levels) as well as the vasorelaxant response induced by the compound were almost completely attenuated in rings in which the vascular endothelium was mechanically removed, endothelium-derived NO seems to be involved in CMMTT action and allowed us to discard a possible NO-donating effect induced by the compound.…”
Section: Discussionmentioning
confidence: 99%